Women in sports : 50 fearless athletes who played to win - Ignotofsky, Rachel, 1989- (London Wren and rook, 2017)
"... highlights the achievements and stories of fifty notable women athletes--from well-known figures like tennis player Billie Jean King and gymnast Simone Biles, to lesser-known athletes like skateboarding pioneer Patti McGee and Toni Stone, the first woman to play baseball in a men's professional league"--Provided by publisher.
Includes bibliographical references (p. 122-125) and index.
Kirkus Review
School Library Journal
Kirkus Review, May 2017
School Library Journal, May 2017
6.1
Keywords: Women athletes -- Biography -- Juvenile literature; Women athletes -- History -- Juvenile literature; Women Olympic athletes -- Biography -- Juvenile literature; Women Olympic athletes -- History -- Juvenile literature; Athletes; Athletes -- History; Olympic athletes; Olympic athletes -- History; Women -- Biography; ART / Popular Culture; Athletes -- Biography; Athletes -- History; Olympic athletes; Olympic athletes -- History; SOCIAL SCIENCE / Women's Studies; SPORTS & RECREATION / History; Women -- Biography; Biographies